Italian consensus recommendations for the management of hepatitis C infection in patients with rheumatoid arthritis. Issue 6 (2nd November 2019) - Sebastiani, Marco; Milazzo, Laura; Atzeni, Fabiola; Vacchi, Caterina; Manfredi, Andreina; Quartuccio, Luca; Scirè, Carlo; Gaeta, Giovanni Battista; Lapadula, Giovanni; Armignacco, Orlando; Tavio, Marcello; D'Angelo, Salvatore; et al.
Abstract: Objectives: The recent introduction of direct-acting antiviral agents (DAAs) which can eliminate Hepatitis C virus (HCV) had revolutionized the treatment of HCV infections also in a complex clinical setting such as the patients with rheumatoid arthritis (RA). HCV elimination is also opportune due to the availability of more efficient immunosuppressive drugs, whose effect on the course of HCV infection is largely unknown. Methods: Consensus process was endorsed by the Italian Society of Rheumatology (SIR) and the Italian Society of Infectious and Tropical Diseases (SIMIT) to review the available evidence and produce practical, hospital-wide recommendations. The consensus panel consisted of 18 infectious diseases consultants, 20 rheumatologists and one clinical epidemiologist, who used the criteria of the Oxford Centre for Evidence-based Medicine to assess the quality of the evidence and the strength of their recommendations. Results: A core-set of statements about management of patients with RA and infection by HCV have been developed to help clinicians in their clinical practice. Conclusions: A screening for HCV should be performed in all RA patients and it is mandatory before starting an immunosuppressive therapy. Finally, a DAA treatment should be considered in all HCV-infected patients. Significance and Innovations: HCV antibodies should be investigated at the time of diagnosis of RA and, in any case, before starting immunosuppressive therapy with disease-modifying antirheumatic drugs (DMARDs). HCV eradication with DAA should be attempted as soon as possible, depending on patient conditions allowing a continuous oral treatment lasting 8–12 weeks Conventional and biological DMARDs are allowed in patients with HCV infection, but they should be used cautiously in presence of advanced liver disease.